Tetrandrine may treat membranous glomerulopathy via P13K/Akt signaling pathway regulation: therapeutic mechanism validation using Heymann nephritis rat model. Issue 1 (1st January 2021) - Yin, Jiazhen; Lin, Jiazhen; Yu, Jin; Wei, Xia; Zhu, Bin; Zhu, Caifeng
ABSTRACT: Membranous glomerulopathy (MGN) is an autoimmune kidney disease that is the primary cause of nephrotic syndrome (NS) in adults. Tetrandrine, a bisbenzylisoquinoline alkaloid, is known to have numerous pharmacological effects. In this study, network pharmacology analysis and experimental validation were conducted to analyze the mechanisms by which tetrandrine functions as a therapeutic intervention for MGN. A systematic network pharmacology method was applied to identify potential targets and determine the therapeutic mechanism of tetrandrine in MGN treatment. A Heymann nephritis (HN) rat model was developed to assess the therapeutic effects of tetrandrine on NS and validate the predicted molecular mechanisms. We obtained 86 potential targets of tetrandrine for the treatment of NS. In vivo experiments showed that tetrandrine could reduce the 24-h urine protein content, decrease glomerular basement membrane proliferation, and significantly decrease thylakoid stroma and cell proliferation in the HN rat kidney tissue. Moreover, tetrandrine suppressed kidney cell apoptosis and upregulated the expression of nephrin and podocin in HN model rats. qRT-PCR results revealed that tetrandrine inhibited IL-1β, TNFα, and MCP-1 levels in HN model rats. Western blot results indicated that tetrandrine can protect against MGN via the PI3K/Akt signaling pathway. Thus, by using a combination of network and experimental pharmacology methods, we demonstrate that tetrandrine can treat MGN via the PI3K/Akt signaling pathway and provide novel insights into the mechanisms underlying tetrandrine-mediated management of MGN. Graphical abstract: uf0001